Natural and Synthetic Inhibitors of Heat Shock Protein 90 Chaperone in Cancer Treatment - Ravula, Shravanthi; Akula, Sravani; Kancha, Rama Krishna (Indian Journal of Pharmaceutical Education and Research, 2024)
The heat shock protein 90 (HSP90) plays a crucial role in regulating cellular homeostasis. Importantly, enhanced dependence of cancer-specific proteins or mutants on HSP90 for their stability and activity offers HSP90 as an attractive therapeutic target. But, HSP90 being an important house-keeping protein, raised skepticism towards achieving cancer-specific therapeutic efficacy. Biochemical and functional studies revealed differential activity of HSP90 between healthy and cancer cells indicating the promise of specific chemical inhibitors in treating the disease. The current educational article elaborates on multiple classes of inhibitors that either have pre-clinical activity or being tested in various phases of clinical trials. In addition, recent pre-clinical findings that offer mechanistic insights into the therapeutic efficacy of HSP90 inhibitors are detailed. Thus, the article focuses on the promise of HSP90 as a therapeutic target and recent advances in the development of novel HSP90 inhibitors. Furthermore, we discuss the genetic factors and molecular mechanisms that influence the success of targeting HSP90 chaperone in cancer treatment.
Keywords: Chaperones; Cancer; Drug resistance; HSP90 inhibitors; Natural products